A comprehensive analysis of the role of TTF2/ Lds throughout the cell cycle - Rahme, Salma (2021)
Coordination of transcription and cell division is critical for life, but how transcription is switched off during mitosis remains unknown. Putative players in this mitotic transcription inactivation (MTI) are the human transcription termination factor 2 (TTF2) and Lodestar (Lds), both considered orthologs genes. Sequencing information is the major premise to support their orthology. In fact, TTF2 and Lds are 39% identical, 56% similar, and belong to the Snf2 helicase-like family. To further corroborate the idea that they are putative orthologs, in addition to their sequence analysis, I reviewed the published literature to discuss their shared functional aspects in particular at transcription and cell division. TTF2/Lds display similar in vitro transcription termination activities supporting being orthologs. Despite termination activity being explored for TTF2 more than Lds, they have dsDNA-dependent ATPase activity, release short transcripts associated with RNA Polymerase II (Pol II) from the DNA template and suppress long transcripts. In addition, TTF2 releases Poll II from the DNA template regardless of the phosphorylation state, and depletion of TTF2 causes retention of Pol II at metaphase chromosomes, implicating TTF2 in MTI. Concerning their functions on cell division, TTF2 is less described than Lds. Both TTF2/Lds depletion causes erroneous chromosome segregation but the degree and type of errors are very different. Due to the limited published data, it is still premature to conclude if they share ortholog mitotic functions. From my study of the available literature, despite TTF2 and Lds orthology being substantiated on their transcription functions, it remains unclear whether mitotic defects associated with TTF2/Lds depletion represent different protein functions, one in transcription and another in faithful chromosome segregation, or instead implies MTI mis-regulation can per se affect mitotic fidelity. Further research is needed to dissect this possible dichotomy, namely by the use of live imaging techniques.